THE INDEPENDENCE PRINCIPLE AND ITS REALISATION IN THE POLICY OF THE EUROPEAN CENTRAL BANK - Mucha-Leszko, Bogumila; Honchar, Oleksandr (Journal of European Economy, 2018)
This paper highlights a role of the European Central Bank’s independence in the process of monetary policy realisation in euro-area. It also includes an analysis and evaluation of the ECB powers.